Legal Status of the Prosecutor’s Office in Ukraine - Lapkin, Andrii (Teisė, 2022)
The scientific article is devoted to the study of the legal status of the Prosecutor’s Office in Ukraine in the context of the development of judicial reform. The historical development of the Prosecutor’s Office during the independence of Ukraine, which was carried out by transforming from the Soviet model of “supervision service” to the model of the “prosecution service” established in Europe, is analyzed. The problems of determining the place of prosecutor’s office in the system of division of state power of Ukraine are investigated. The understanding of the prosecutor’s office as adjacent to the judicial authority of the legal institute is substantiated. The purpose and objectives of the prosecutor’s office, as well as the system of its functions, are described. The problems of functional appointment of the prosecutor’s office, as well as regulation of its functions are revealed. The system of prosecutor’s office is defined and its elements are characterized. The main links of the prosecutor’s office, as well as the division of prosecutors into territorial and specialized ones are investigated.